Ordinatio ad Casum: Legal Causation in Italy (14th–17th Centuries) - Rossi, Guido, (Klostermann, 2023)
The book examines the development of legal causation in Italy from the fourteenth to the seventeenth centuries, focusing especially on practice-oriented literature (decisiones and consilia). Causality began to be discussed from the late thirteenth century and especially during the first half of the fourteenth when it was described as ordinatio. In private law, ordinatio remained the standard approach to causation during the entire early modern period: centuries of legal practice mainly refined its scope but did not change its core. By contrast, its application in criminal law would increasingly crash with the intentionality requirement, and so it was progressively challenged.